Karyotype differentiation of three anopheline taxa in the balabacensis complex of Southeast Asia (Diptera: Culicidae) - V. Baimai (2018)
Cytological studies of the mitotic and meiotic karyotypes and the polytene salivary chromosomes of Anopheles dirus, An. takasagoensis and An. balabacensis (Perlis form), have revealed significant differences in the sex chromosomes. These differences are largely due to the position of the centromere and different amounts of constitutive heterochromatin and euchromatin. The chromosomal data suggest that An. dirus and An. takasagoensis are more closely related to each other than either is to An. balabacensis (Perlis form). The karyological differences are very useful in differentiating these taxa, particularly the Perlis form, and lend support for their species status. © 1981 Dr W. Junk Publishers.